Pelatihan dan Penyuluhan Dalam Peningkatan Kualitas Hidup Lansia Melalui Pemanfaatan Posyandu Cekke Kab. Enrekang - Yusnayanti, Cici; Manang, Imran; Pannyiwi, Rahmat; Ishmatika, Enka Nur; Treasa, Adisty Dwi; Malaha, Naomi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
The elderly are individuals aged 60 years and over, who generally have signs of decline in biological, psychological, social and economic functions. The aim of this Community Service is to improve the quality of life through improving health and welfare, especially for the elderly, elderly families, posyandu cadres and stakeholders in the Cekke Posyandu working area. The facilities and infrastructure provided by regional and village governments can be put to good use by the community. This Community Service Activity Method is carried out by providing counseling to the elderly, elderly families, posyandu cadres and traditional stakeholders or community leaders. After receiving the counseling, the elderly can understand well the benefits of the elderly posyandu, which has always been in their minds, which is reflected in this activity. just weighing yourself. As a result of following the training and counseling, these elderly people were able to understand and understand more fully the benefits of this elderly posyandu. It is hoped that posyandu cadres, families of the elderly and stakeholders can actively participate in helping to utilize the posyandu for the elderly.